THE EFFECT OF FREELETIC EXERCISE ON LEG STRENGTH IN THE FREELETIC COMMUNITY OF MAKASSAR - Irianto irianto; Hastuti Hastuti (Nusantara Medical Science Journal, 2018)
Introduction: Any human exercise will always involve physical conditions in it. there are 10 kinds of components of physical condition, that is strength, endurance, muscle power, speed, flexibility, agility, coordination, balance, accuracy, and reaction. Limb muscles play a leading role in many sports. To improve and develop the physical condition of an athlete, it takes an exercise, an exercise that someone has to do continuously in order to produce maximum movement. Freeletic exercise is one of the techniques used to increase leg muscle strength. This study aims to determine differences in leg muscle strength in freeletic members Makassar before and after the provision of freeletic exercise. Methods: This study is Pre Exsperimental and using one group pre-post test design. The sampling technique is purposive sampling with the number of samples is 20 people based on the inclusion and exclusion criteria for 6 weeks. Measuring tool used is Leg Dynamometer and Squat Test to know the value of muscle strength of limb before and after 18 practice. Results: The results showed there is an effect of freeletic sport to increase legs muscle strength after given 18 times freeletic sport practice with value of P<0,001.